In Vitro Anti-Inflammatory Effects of Three Fatty Acids from Royal Jelly - Yi-Fan Chen; Kai Wang; Yan-Zheng Zhang; Yu-Fei Zheng; Fu-Liang Hu (Hindawi Limited, 2016)
Trans-10-hydroxy-2-decenoic acid (10-H2DA), 10-hydroxydecanoic acid (10-HDAA), and sebacic acid (SEA) are the three major fatty acids in royal jelly (RJ). Previous studies have revealed several pharmacological activities of 10-H2DA and 10-HDAA, although the anti-inflammatory effects and underlying mechanisms by which SEA acts are poorly understood. In the present study, we evaluated and compared the in vitro anti-inflammatory effects of these RJ fatty acids in lipopolysaccharide-stimulated RAW 264.7 macrophages. The results showed that 10-H2DA, 10-HDAA, and SEA had potent, dose-dependent inhibitory effects on the release of the major inflammatory-mediators, nitric oxide, and interleukin-10, and only SEA decreased TNF-α production. Several key inflammatory genes have also been modulated by these RJ fatty acids, with 10-H2DA showing distinct modulating effects as compared to the other two FAs. Furthermore, we found that these three FAs regulated several proteins involved in MAPK and NF-κB signaling pathways. Taken together, these findings provide additional references for using RJ against inflammatory diseases.